2020
DOI: 10.1186/s13063-020-4211-9
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and cost-effectiveness of a Victim Improvement Package (VIP) for the reduction of chronic symptoms of depression or anxiety in older victims of common crime (the VIP trial): study protocol for a randomised controlled trial

Abstract: Background: Older people are vulnerable to sustained high levels of psychosocial distress following a crime. A cognitive behavioural therapy (CBT)-informed psychological therapy, the Victim Improvement Package (VIP) may aid recovery. The VIP trial aims to test the clinical and cost-effectiveness of the VIP for alleviating depressive and anxiety symptoms in older victims of crime. Methods/design: People aged 65 years or more who report being a victim of crime will be screened by Metropolitan Police Service Safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Sexual health promotion intervention for people with severe mental illness [78] Self-harm, suicide attempt, violence to others or victim of violence CBT for chronic symptoms of depression or anxiety in older victims of common crime [39] ICH GCP definition plus any important medical event that may jeopardize the participant or may require an intervention to prevent one of the above characteristics/consequences.…”
Section: Stigmatization Of Overweight/underweight Children 4 Noticeable Weight Lossmentioning
confidence: 99%
“…Sexual health promotion intervention for people with severe mental illness [78] Self-harm, suicide attempt, violence to others or victim of violence CBT for chronic symptoms of depression or anxiety in older victims of common crime [39] ICH GCP definition plus any important medical event that may jeopardize the participant or may require an intervention to prevent one of the above characteristics/consequences.…”
Section: Stigmatization Of Overweight/underweight Children 4 Noticeable Weight Lossmentioning
confidence: 99%
“…In total, 34 documents 40–73 identified from systematic and cluster searches informed the development of CMOCs. This evidence comprised peer‐reviewed journal articles (primary research, study protocol), service level reports and evaluations, published between 1990 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…However, this approach was often lacking in the existing interventions. Interventions that rely solely on distributing information may not be sufficient, as this places the burden on individuals to be proactive in seeking help 68 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardizing assessment and intervention to 3 months post-incident has been recommended in other trauma populations as it allows time for natural recovery without prolonging suffering in victims with continued symptoms (McNally et al, 2003). This would also build on existing research identified in this review (Serfaty et al, 2016(Serfaty et al, , 2020.…”
Section: Discussionmentioning
confidence: 95%